EKSISTENSI PEREMPUAN DALAM NOVEL MIDAH SIMANIS BERGIGI EMAS KARYA PRAMOEDYA ANANTA TOER: KAJIAN SASTRA FEMINIS - Irham Nurfaizin; Suprapto Suprapto (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2021)
This research focuses on research on feminism. This research aims to a). describe forms of gender inequality in female characters, and b) Describe the existence of female main characters. This research analysis uses a qualitative descriptive research method, namely data in the form of words and sentences rather than numbers as the data results. Data collection techniques using listening and note-taking techniques. Meanwhile, the data analysis for this research was carried out in a structured manner; namely collecting data by translating the dialogue of the Budhi Wijaya ludruk players, reducing the data, and analyzing the data and drawing conclusions. The object of this research is the novel Midah Simanis Bergigi Gigi by Pramoedya Ananta Toer. From the analysis carried out on the novel Midah Simanis Bergigi Emas, it was concluded that the main female character, Midah, succeeded in achieving transcendence and transformation of society. This is based on strategies from Simone de Beavoir with research results, namely; a) The existence of gender inequality in the novel Midah Simanis Bergigi Emas (Subordination, Stereotypes, Marginalization, excessive workload, violence). b) The existence of women in Midah Simanis's novel Gold Teeth (women work, women are hard workers, women become intellectuals, and women gain societal transformation). The conclusion of this research is that there is unfair behavior towards female characters in the novel Midah Simanis Bergigi Emas.Key words: Women, Feminist Movement, Existence